INTRODUCTION TO HEALTHY LOW-SUGAR FOODS USING ARTIFICIAL NEURAL NETWORKS WITH THE PERCEPTRON METHOD - Wirayudha, Wendy; Hastono, Tri; Mujahidin, Mujahidin (JTH: Journal of Technology and Health, 2023)
With tecnology, the figuring system has become simpler. Tecnology are utilized to demonstrate the organic nerves of the human mind, Tecnology are prepared and shown the proper behavior like human nerve cells that can perceive basic examples. Counterfeit brain networks can perceive input examples and will give yield that matches the objective to be accomplished. In this review, the Perceptron technique was utilized to distinguish input designs as sound, low-cholesterol food varieties. This technique works by changing the contribution to the objective and changing the loads until no more mistakes are tracked down in every age. This side effect of serving a low-sugar diet shows that meat, fresh fish, and vegetables are food sources that contain high levels of sugar. Keyword: neural networks, perceptron, sugar.